2014
DOI: 10.1063/1.4890105
|View full text |Cite
|
Sign up to set email alerts
|

X-ray excited ZnS:Cu,Co afterglow nanoparticles for photodynamic activation

Abstract: Copper and cobalt co-doped ZnS (ZnS:Cu,Co) afterglow nanoparticles were conjugated to photosensitizer tetrabromorhodamine-123 (TBrRh123) and efficient energy transfer from the nanoparticles to TBrRh123 was observed. In addition to their X-ray excited luminescence, the ZnS:Cu,Co nanoparticles also show long lasting afterglow, which continuously serve as a light source for photodynamic therapy (PDT) activation. Compared to TBrRh123 or ZnS:Cu,Co alone, the ZnS:Cu,Co-TBrRh123 conjugates show low dark toxicity but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 28 publications
1
76
0
1
Order By: Relevance
“…109 In this work, tetrabromorhodamine-123 (TBrRh123) was conjugated to copper and cobalt co-doped ZnS (ZnS:Cu,Co). Results showed the combination had an efficient energy transfer and also displayed a long lasting afterglow, which could be a persistent light source for PDT even when the X-rays were turned off.…”
Section: X-ray Induced Photodynamic Therapymentioning
confidence: 99%
“…109 In this work, tetrabromorhodamine-123 (TBrRh123) was conjugated to copper and cobalt co-doped ZnS (ZnS:Cu,Co). Results showed the combination had an efficient energy transfer and also displayed a long lasting afterglow, which could be a persistent light source for PDT even when the X-rays were turned off.…”
Section: X-ray Induced Photodynamic Therapymentioning
confidence: 99%
“…It also should be pointed out that nanomedicine has become a hot area that under extensive investigations. [213][214][215][216][217][218][219][220][221][222][223][224][225][226][227][228][229] In addition to use nanoparticles for radiation enhancement discussed above, the combination of radiotherapy and photodynamic therapy via nanoparticles have been proposed and investigated. 220-229 Nanomedicine will have a bright future and will help to accelerate the progress toward ending cancers.…”
Section: Cscs Biomarkersmentioning
confidence: 99%
“…Zhang et al showed that a cyan persistent luminescence can be discerned in La 3 GaGe 5 O 16 [24]. Upon doping with Cr 3+ , the characteristic deep red emission is observed along with an enhancement of the intensity of the persistent luminescence.…”
mentioning
confidence: 99%
“…The delay can amount to minutes, hours or even days, which is exploited in emergency and safety signage, bioimaging, watch dials, toys, surveillance applications, counterfeiting and as light source for photodynamic activation to treat cancers and other diseases [1][2][3]. The defects, or traps, present in a persistent phosphor can store excitation energy under the form of trapped charge carriers.…”
Section: Introductionmentioning
confidence: 99%